2003
DOI: 10.1089/08977150360517236
|View full text |Cite
|
Sign up to set email alerts
|

Delayed Treatment of Hemoglobin Neurotoxicity

Abstract: Hemoglobin is an oxidative neurotoxin that may contribute to cell injury after CNS trauma and hemorrhagic stroke. Prior studies have demonstrated that concomitant treatment with iron-chelating antioxidants prevents its neurotoxicity. However, the efficacy of these agents when applied hours after hemoglobin has not been determined, and is the subject of the present investigation. Consistent with prior observations, an increase in reactive oxygen species generation, detected by 2',7'-dichlorofluorescin oxidation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
31
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
3
2

Relationship

1
9

Authors

Journals

citations
Cited by 63 publications
(31 citation statements)
references
References 38 publications
0
31
0
Order By: Relevance
“…Regan and Rogers showed that delayed treatment with deferoxamine markedly attenuates the production of reactive oxygen species and neuronal death induced by adding hemoglobin to mixed neuronal and astrocyte cell cultures 10 and that deferoxamine attenuates the effects of hemoglobin, which potentiates the neurotoxicity of glutamate agonists in murine cortical cultures. 3 Deferoxamine also reduces the production of reactive oxygen species and cell death induced by hemin in human neuron-like cells 4 and pheochromocytoma and neuroblastoma cell lines.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…Regan and Rogers showed that delayed treatment with deferoxamine markedly attenuates the production of reactive oxygen species and neuronal death induced by adding hemoglobin to mixed neuronal and astrocyte cell cultures 10 and that deferoxamine attenuates the effects of hemoglobin, which potentiates the neurotoxicity of glutamate agonists in murine cortical cultures. 3 Deferoxamine also reduces the production of reactive oxygen species and cell death induced by hemin in human neuron-like cells 4 and pheochromocytoma and neuroblastoma cell lines.…”
Section: In Vitro Studiesmentioning
confidence: 99%
“…It attenuates oxidative stress in cultured neurons and astrocytes, likely a result of reducing the amount of iron available to generate free radicals. 133 It may also confer added protection to the injured immature brain by upregulating hypoxia-inducible factor-1, which promotes cell survival via the activation of molecules such as erythropoetin and vascular endothelial growth factor. 134 This later phenomenon is supported in a recent in vitro study of ischemic injury where the beneficial effects of deferoxamine in reducing hippocampal neuronal death were diminished in the presence of an antisense oligonucleotide specific for hypoxia-inducible factor-1alpha.…”
Section: Iron Accumulation In the Injured Brainmentioning
confidence: 99%
“…8, 9 This effect is mitigated by protein or low molecular weight iron chelators, resulting in net neuroprotection that may be mediated by the other reaction products. 3, 10, 11 Astrocytes, which are relatively resistant to acute iron toxicity due to ferritin induction, 12 are protected from hemin by both HO-1 and HO-2 in the absence of exogenous chelators. 13, 14 The effect of HO expression in any model may therefore depend on the cell population at greatest risk and the iron binding capacity of the cellular microenvironment.…”
Section: Introductionmentioning
confidence: 99%